2021
DOI: 10.3389/fmed.2021.672257
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Normoxia, Hyperoxia, and Mild Hypoxia on Macro-Hemodynamics and the Skeletal Muscle Microcirculation in Anesthetised Rats

Abstract: Objectives: Excessive oxygen (O2) administration may have a negative impact on tissue perfusion by inducing vasoconstriction and oxidative stress. We aimed to evaluate the effects of different inhaled oxygen fractions (FiO2) on macro-hemodynamics and microvascular perfusion in a rat model.Methods: Isoflurane-anesthetised spontaneously breathing male Wistar rats were equipped with arterial (carotid artery) and venous (jugular vein) catheters and tracheotomy, and randomized into three groups: normoxia (FiO2 21%,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 39 publications
0
8
0
1
Order By: Relevance
“…Additionally, an animal study showed that in swine who were mildly hypoxemic at rest, myocardial oxygenation was still maintained during a 60-s period of apnea, despite a significantly greater blood desaturation than observed during apnea conducted at normoxemia [41]. Other studies have looked at the protective effect of hypercapnia or mild hypoxemia on the skeletal microvascular function [42] and the brain. For example, in a rat model assessing cerebral ischemia, hypercapnia was found to be therapeutic under mild-to-moderate hypoxemia, although detrimental when combined with severe hypoxemia (PaO 2 < 50 mmHg) [43].…”
Section: Impact Of Blood Gas Changes On Steady-state Blood Flowmentioning
confidence: 99%
“…Additionally, an animal study showed that in swine who were mildly hypoxemic at rest, myocardial oxygenation was still maintained during a 60-s period of apnea, despite a significantly greater blood desaturation than observed during apnea conducted at normoxemia [41]. Other studies have looked at the protective effect of hypercapnia or mild hypoxemia on the skeletal microvascular function [42] and the brain. For example, in a rat model assessing cerebral ischemia, hypercapnia was found to be therapeutic under mild-to-moderate hypoxemia, although detrimental when combined with severe hypoxemia (PaO 2 < 50 mmHg) [43].…”
Section: Impact Of Blood Gas Changes On Steady-state Blood Flowmentioning
confidence: 99%
“…The use of direct visualization techniques to guide resuscitation in sepsis faces several barriers despite the improvement of quality imaging devices and automated analysis tools [26,27]. The patients tongue needs to remain immobile for at least 5 s to acquire adequate quality video sequences.…”
Section: Microcirculationmentioning
confidence: 99%
“…Our data are comparable with those from other studies on the same species and strain of rat ( Table 1 ). 12 13 14 15 16 The average pH values determined at T0’ (pre-treatment), T30’, and T60’ are 7.45 ± 0.046, 7.25 ± 0.11, and 7.22 ± 0.09, respectively ( Figure 1A ). Values which differ significantly from the initial pH (T0’) ( P < 0.05) are still within the tolerated range for the organism, since they can be compensated by physiological buffers.…”
Section: R Esultsmentioning
confidence: 99%